Different Circulation Pattern of Multiple Respiratory Viruses in Southern China During the COVID-19 Pandemic - Zeng, Zhiqi; Guan, Wenda; Liu, Yong; Lin, Zhengshi; Liang, Wenhua; Liang, Jingyi; Chen, Bingqian; Wu, Tong; Wang, Yutao; Yang, Chunguang; Wu, Qiubao; Mai, Zhitong; et al. (Frontiers in Microbiology, 2022)
China implemented stringent non-pharmaceutical interventions (NPIs) in spring 2020, which has effectively suppressed SARS-CoV-2. In this study, we utilized data from routine respiratory virus testing requests from physicians and examined circulation of 11 other respiratory viruses in Southern China, from January 1, 2018 to December 31, 2020. A total of 58,169 throat swabs from patients with acute respiratory tract infections (ARTIs) were collected and tested. We found that while the overall activity of respiratory viruses was lower during the period with stringent NPIs, virus activity rebounded shortly after the NPIs were relaxed and social activities resumed. Only influenza was effectively suppressed with very low circulation which extended to the end of 2020. Circulation of other respiratory viruses in the community was maintained even during the period of stringent interventions, especially for rhinovirus. Our study shows that NPIs against COVID-19 have different impacts on respiratory viruses.